Media Restrictions on Papua – Understanding the Impacts - Abplanalp, Karen (Auckland University of Technology, 2015)
Indonesia has restricted access for journalists seeking to visit West Papua for more than 50 years. On May 10, 2015, shortly after this thesis was submitted, Indonesia’s President, Joko Widodo, announced the media restrictions on Papua were to be lifted. The apparent change in policy is yet to be tested. According to Papuan journalist Victor Mambor, no foreign journalist has tried to visit Papua since Widodo’s statement (Mambor, personal communication, June 19, 2015). Using the concepts of Peace Journalism, this research exegesis and microsite artefact seeks to examine the impact the media restrictions have had on the quality and type of journalism produced about West Papua, and also on the public’s opinion of Indonesia. The research is largely drawn from a case study involving 10 journalists from West Papua, Indonesia, New Zealand and Australia – all of whom report about West Papua. The author is also a participant in this study. The thesis includes a web-based artifact incorporating a series of video interviews with the 10 journalists. This thesis finds that media restrictions directly impact on the quality of journalism produced about West Papua and create serious risks for journalists and their sources, and impact negatively on Indonesia’s international image. If the aim of the restrictions is to control and limit negative reportage about West Papua, then this study finds that they do the opposite. The media constraints severely limit the possibility of positive and unbiased reportage. The study provides suggestions on how to mitigate these risks. [Note: Please contact the author, Karen Abplanalp at: karen.abplanalp@gmail.com for access to the microsite artefact (a website) created by the author.]
Keywords: Papua, West Papua; Indonesia; Asia Pacific; Peace journalism; Journalism; Human rights; Media freedom; Media restrictions